My internship ’sans’ residents - Shankar, P Ravi (Research and Humanities in Medical Education, 2021)
During internship, newly graduated doctors practice under supervision to apply knowledge and skills along with a proper, ethical attitude in the treatment of patients. The Government Medical College, Thrissur, located in Kerala, India, was started in the year 1981. The institution did not have postgraduate students / residents for several years during the initial phase. In this article the author describes his internship experience at the institution in the nineties. There were advantages to not having residents in terms of greater opportunities for patient care and for ‘doing’ different procedures. Closer relationships were forged with faculty members. The drawback was the lack of a group of doctors closer to oneself in age and training who could provide practical tips and advice from a near-peer perspective.